STUDIES ON PRESENCE OF SEMIOCHEMICALS FROM PHENACOCCUS SOLENOPSIS (TINSLEY) - ANITA SINGH; DOLLY KUMAR (International Journal of Pharma and Bio Sciences, 2015)
The mealybug, Phenacoccus solenopsis (Tinsley), is a serious pest in Vadodara agricultural fields in India. In an attempt to find solutions to reduce the infestation by this pest,simple behavioural bioassays were conducted under the laboratory conditions using semiochemicals obtained through n-hexane solvent- volatile extract of female Phenacoccus solenopsis. Observations were made at the rate of attraction of male and female of mealybug towards female volatile extracts which was isolated by both confinement and adsorbent methods. The result obtained during behavioural bioassay showed that the attractive index of males towards female volatile extract collected from adsorbent method was higher (0.86) than the females. This indicated the presence of a semiochemicals as a sex attractant in the female volatile extract which could attract comparatively more males. The further isolation of volatile extract by using GC-MS shows the presence of ester and terpenes compound. Hence, the information contained in this paper pave way to the identification of proper management practices to maximize lure methods during effective reproductive period and also useful in providing good scope for further development of ecofriendly methods for Phenacoccus solenopsis control.